Do True and False Intentions Differ in Level of Abstraction? A Test of Construal Level Theory in Deception Contexts - Calderon, Sofia; Mac Giolla, Erik; Granhag, Pär Anders; Ask, Karl (Frontiers in Psychology, 2017)
The aim was to examine how people mentally represent alleged future actions—their true and false intentions. In two experiments, participants were asked to either tell the truth (i.e., express true intentions) or lie (i.e., express false intentions) about performing future tasks. Drawing on Construal Level Theory, which proposes that psychologically distant events are more abstractly construed than proximal ones, it was predicted that liars would have more abstract mental representations of the future tasks than truth tellers, due to differences in hypotheticality (i.e., the likelihood of the future tasks occurring). Construal level was measured by a video segmentation task (Experiment 1, N = 125) and preference for abstract or concrete descriptions of tasks (Experiment 2, N = 59). Veracity had no effect on construal level. Speaking against our initial predictions, the data indicate that true and false intentions are construed at similar levels of abstraction. The results are discussed in the light of Construal Level Theory and the emerging psycho-legal research on true and false intentions.